Analisis Faktor yang Mempengaruhi Peran Perawat Dalam Pencegahan Medication Error Diruang Rawat Inap Rumah Sakit Awal Bros Batam : Analysis of Factors Influencing the Role of Nurses in Prevention Medication Error in the Inpatient Room of Awal Bros Batam Hospital - Novi Yulianti; Hema Malini; Sri Muharni (NERS Jurnal Keperawatan, 2019)
Medication Error is an event that not only can harm the patient but also may endanger the safety of patients conducted by health workers, especially for patient safety. This study aims to examine and analyze the role of factors that contribute to the nurse's role in preventing medication error in hospitals Awal Bros Batam. This research method is quantitative using observational analytic study design to examine the relationship between the two variables studied. This research was conducted on a sample of 73 nurses at the Awal Bros Batam inpatient room consisting of six general rooms and two high-care units. The results of this study indicate that the statistical test showed p-value = 0.042; thus, there is no significant correlation between the perception of the workload with the role of nurses. There is a significant relationship of knowledge to the role of nurses p-value = 0.014, no significant association between the attitudes of nurses with nurse's role p-value = 0.009. The further recommendation to the hospital improves medication safety at the inpatient ward Awal Bros Batam Hospital, to use unit-dose dispensing system (UDD), as well as the use of electronic in the form of barcodes.